Review of anti-vascular endothelial growth factor therapy in macular edema secondary to central retinal vein occlusions. (December 2011) - Mitra, Arijit; Lip, Peck-Lin
Central retinal vein occlusion (CRVO) is a common retinal vascular disorder with potential risk of blindness. CRVO can be categorized into two distinct entities – non-ischemic and ischemic. Visual prognosis depends on the type of retinal vein occlusion, its severity, degree of retinal ischemia or macular edema (ME) and development of complications. The two most frequent complications of CRVO are persistent ME and neovascularization. Until recently, there has been no effective treatment for ME in CRVO. The introduction of anti-VEGF therapy has altered treatment options for this disease entity. This article aims to review the effect of anti-VEGF drugs in promoting the resolution of edema and improving vision in patients with ME in CRVO.